2009
DOI: 10.1681/asn.2008080870
|View full text |Cite
|
Sign up to set email alerts
|

Agalsidase Alfa and Kidney Dysfunction in Fabry Disease

Abstract: In male patients with Fabry disease, an X-linked disorder of glycosphingolipid metabolism caused by deficient activity of the lysosomal enzyme ␣-galactosidase A, kidney dysfunction becomes apparent by the third decade of life and invariably progresses to ESRD without treatment. Here, we summarize the effects of agalsidase alfa on kidney function from three prospective, randomized, placebo-controlled trials and their open-label extension studies involving 108 adult male patients. The mean baseline GFR among 54 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 29 publications
2
126
1
3
Order By: Relevance
“…Given the substantial heterogeneity in our patient population and lack of pre-enrollment renal history, it is difficult to compare these outcomes with those reported in previous clinical trials and observational studies of either agala or agalb. However, our results are generally similar to those from previous studies with agala or agalb, which have shown positive effects of ERT to slow down the decline of eGFR Germain et al 2007;Mehta et al 2009;West et al 2009;Rombach et al 2013;Weidemann et al 2013;Anderson et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Given the substantial heterogeneity in our patient population and lack of pre-enrollment renal history, it is difficult to compare these outcomes with those reported in previous clinical trials and observational studies of either agala or agalb. However, our results are generally similar to those from previous studies with agala or agalb, which have shown positive effects of ERT to slow down the decline of eGFR Germain et al 2007;Mehta et al 2009;West et al 2009;Rombach et al 2013;Weidemann et al 2013;Anderson et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…A previous analysis of pooled data from three randomized, placebo-controlled clinical trials and their open-label extensions (sponsored by Shire Human Genetic Therapies) of male patients with Fabry disease suggested a stabilizing effect of agalsidase alfa (agalα) on renal function assessed by measured glomerular filtration rate (GFR). 11 In that analysis, baseline GFR or elevated proteinuria category (≥1 g/24 h) significantly predicted GFR decline during treatment. Using a suitable selection approach of pooled data Purpose: Globotriaosylceramide concentrations were assessed as potential predictors of change from baseline after 12 months by estimated glomerular filtration rate and left-ventricular mass index using pooled data from three randomized, placebo-controlled agalsidase alfa trials and open-label extensions of patients with Fabry disease.…”
Section: Original Research Articlementioning
confidence: 91%
“…This leads to progressive accumulation of glycosphingolipids, particularly globotriaosylceramide, in almost all tissues and organs. The most serious complications in adult patients are progressive renal impairment, cardiomyopathy, and cerebrovascular events, all of which lead to significant morbidity and mortality and reduced life expectancy [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%